PENGARUH GAYA KOMUNIKASI PRESENTER TALKSHOW “RUMPI NO SECRET” DI TRANS TV TERHADAP AUDIENCE SATISFACTION - Kurniawan Prasetyo (Universitas Mercu Buana, 2019)
Television stations every day present various types of programs whose types are very diverse. One of them is a talk show program. One of the talk show programs. the mainstay of Trans TV is